Studi Fenomenologis tentang Dampak Bermain Mobile Legends terhadap Motivasi dan Disiplin Belajar Mahasiswa Universitas KH. A. Wahab Hasbullah - Muhammad Aditya Firmansyah; Septian Ragil Anandita (Lembaga Yasin AlSys, 2026)
The high intensity of playing Mobile Legends has the potential to disrupt students’ academic life balance, particularly in terms of learning motivation and discipline. This study aims to examine in depth the impact of Mobile Legends gaming experiences on the learning motivation and discipline of students at Universitas KH. A. Wahab Hasbullah. The study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, participant observation, and documentation involving students who actively played Mobile Legends. The findings indicate that the game has a dual impact on students’ academic lives. On the one hand, Mobile Legends can enhance learning motivation by fostering a competitive spirit and providing mental relaxation. On the other hand, excessive gaming can reduce learning discipline by triggering procrastination and disrupting regular study schedules. These findings affirm that the impact of Mobile Legends on learning motivation and discipline is not absolute but depends on each individual’s self-control and time-management abilities. This study provides practical implications regarding the importance of strengthening self-regulation by establishing strict gaming time limits and the need for educational institutions to provide time-management education so that digital entertainment does not hinder students’ academic productivity.